2016
DOI: 10.1186/s13662-016-0896-1
|View full text |Cite
|
Sign up to set email alerts
|

Some identities of Laguerre polynomials arising from differential equations

Abstract: In this paper, we derive a family of ordinary differential equations from the generating function of the Laguerre polynomials. Then these differential equations are used in order to obtain some properties and new identities for those polynomials.MSC: 05A19; 33C45; 11B37; 35G35

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
(5 reference statements)
0
16
0
Order By: Relevance
“…See [11,Theorem 7]. It is clear that the quantities a i (n) defined by (6.1) play a key role in the above-mentioned conclusions obtained in the paper [11]. However, the quantities a i (n) are expressed complicatedly and can not be computed easily.…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…See [11,Theorem 7]. It is clear that the quantities a i (n) defined by (6.1) play a key role in the above-mentioned conclusions obtained in the paper [11]. However, the quantities a i (n) are expressed complicatedly and can not be computed easily.…”
Section: Remarksmentioning
confidence: 99%
“…Now we explain the motivation of Theorem 3.1 as follows. In [11], the following results were inductively and recursively obtained.…”
Section: Remarksmentioning
confidence: 99%
“…New identities were obtained for degenerate Daehee numbers [8] and for Frobenius-Euler polynomials [9] using linear and nonlinear differential equations. Using differential equations, new identities for Bernoulli numbers of the second kind were obtained in [12], for degenerate Euler numbers and polynomials in [14], and for Laguerre polynomials in [18]. Jang and Kim presented some identities of the ordered Bell numbers arising from differential equation [7].…”
Section: Introductionmentioning
confidence: 99%
“…In [17], Kim et al showed that the following identity holds for the Bernoulli numbers of the second kind…”
Section: Introductionmentioning
confidence: 99%
“…This idea of obtaining some interesting combinatorial identities by using differential equations satisfied by the generating function of special numbers or special polynomials turned out to be very fruitful (see [7,11,13,15]). …”
Section: Introductionmentioning
confidence: 99%